Co-detection of Group A Streptococcus and Viruses in Children with Pharyngitis. (4th October 2017) - Ivaska, Lauri; Gröndahl-Yli-Hannuksela, Kirsi; Niemelä, Jussi; Waris, Matti; Vuorinen, Tytti; Putkuri, Niina; Rantakokko-Jalava, Kaisu; Vuopio, Jaana; Peltola, Ville
Abstract: Background: Co-detection of group A streptococcus (GAS) and viruses in children with pharyngitis has not been well documented. We aimed to study the occurrence of co-detection in relation to GAS diagnostic method and GAS emm types. Methods: This was part of a prospective study done in an emergency department (ED) in febrile children 1–16 years of age with pharyngitis. Throat swabs and blood samples were collected and testing for GAS was performed by 2 different rapid antigen detection tests (RADTs; StrepTop and mariPOC) in the ED and by throat culture in laboratory. In addition, frozen throat swabs were tested for GAS by two different nucleic acid amplification tests (NAAT; Focus 3M and Illumigene). Emm typing of GAS strains was performed from frozen isolates. Virus diagnostics was performed by NAAT and serology, and interferon response to virus infection was estimated by myxovirus resistance protein A (MxA) blood concentration. Results: In total, 83 children (median age 5.5 years; interquartile range 3.2–12.2) were recruited in the study. Specimens from 78 and 48 patients were available for RADT and NAAT, respectively, and 13/19 of GAS isolates for emm typing. In comparison with throat culture results, sensitivities and specificities of GAS diagnostic tests were 72% and 100% for StrepTop, 100% and 72% for mariPOC, 91% and 87% for Focus 3M and 91% and 96% for Illumigene, respectively. In GAS positive patients, virus detection and elevated blood MxA level (≥175 µg/L) were more frequent when GAS diagnosis was based on mariPOC (54.5%) than when it was based on StrepTop (38.5%) test results. Emm types 12, 28 and 89 were detected. GAS emm type 89 was detected in 7 patients of whom 6 had also a positive result in virus detection ( P = 0.053). Conclusion: In comparison with throat culture, diagnostic performance of different GAS tests varies greatly. In children with febrile pharyngitis, enhanced sensitivity of the GAS test seems to be associated with increased co-detection of viruses and interferon responses questioning the significance of GAS detection as a true causative agent in these patients. Detection of GAS emm type 89 was associated with GAS-virus co-detection. Disclosures: All authors: No reported disclosures.